Unenhanced MR Angiography of the Thoracic Aorta: Initial Clinical Evaluation - Francois, Christopher J; Tuite, David; Deshpande, Vibhas; Jerecic, Renate; Weale, Peter; Carr, James C (American journal of roentgenology (1976), 2008)
In patients with difficult i.v. access or renal insufficiency, or in those who are pregnant, we hypothesized than an unenhanced 3D segmented steady-state free precession (SSFP) MR angiography (MRA) technique would be an alternative to contrast-enhanced MR angiography (CE-MRA) for the evaluation of vasculature. MRA examinations of the thoracic aorta were retrospectively reviewed in 23 patients in whom both CE-MRA and 3D SSFP were performed. CE-MRA was performed using an ECG-gated gradient-echo FLASH sequence. Three-dimensional SSFP MRA was performed during free breathing using a motion-adaptive navigator technique. Quantitative assessment of the 3D SSFP and CE-MRA image sets was performed by comparing the aortic lumen diameter. The quality of the images of the aortic root (scale of 1-5) and the presence of cardiovascular and noncardiovascular pathology were independently determined for both techniques by two reviewers. Bland-Altman and Wilcoxon's signed-rank analyses were performed. The difference in orthogonal measurements of the aortic diameter between those made on images from the 3D SSFP and those made from the CE-MRA sequences was -0.042 cm. The aortic root was better visualized with 3D SSFP: score of 3.78 (of 5) for CE-MRA versus score of 4.65 (of 5) for 3D SSFP (p < 0.05). In patients in whom contrast material is contraindicated, unenhanced MRA using a 3D SSFP technique can be performed.